A Not-So-Unexciting Life : Essays on Benedictine History and Spirituality in Honor of Michael Casey, OCSO - Posa, Carmel; Casey, Michael, 1942- (Book collections on Project MUSE., 2017)
This volume, written by eighteen monks, nuns, and lay scholars from seven countries and four continents, aims to recognize the contribution that Michael Casey has made to Cistercian and Benedictine life over the past forty years. Acclaimed as one of today's most significant writers in the Benedictine and Cistercian tradition, Casey has published over one hundred articles and reviews in various journals, written more than eighteen books, and edited many more books and journals. He is a world-renowned retreat master, lecturer, and formator. Book jacket.